Penerapan Metode Pembelajaran Aktif Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa di Mata Pelajaran Pendidikan Kewarganegaraan (PKN) Siswa Kelas 12 SMA 1 DIPONEGORO SEMARANG - Arianadinhaq Muarifin; Desty Endrawati Subroto; Siti Fiyani Istniyati; Melfa Nur Rahmadani; Arini Fauziah; Siti Nafisa Aulia (Kampus Akademik Publiser, 2025)
This study aims to analyze the implementation of active learning methods in improving critical thinking skills in the subject of Civics Education (PKN) among 12th-grade students at SMA 1 Diponegoro Semarang. Active learning is an approach that directly involves students in the learning process through discussions, group work, and problem-solving, allowing them to actively engage in exploring the material. The subjects of this study were 12th-grade students at SMA 1 Diponegoro Semarang. Data were collected through a critical thinking questionnaire test in the Civics subject. The results of the study show that the implementation of active learning methods in Civics significantly improves students' critical thinking skills, as reflected in the increased critical thinking scores on each question. Additionally, students also demonstrated higher interest and motivation to learn. This study recommends the consistent application of active learning methods to foster the development of students' critical thinking skills across various subjects.